Improvement of umbilical hernia repair in one day surgery - E. P. Krivoschekov; M. Yu. Khoroshilov; M. A. Molchanov; V. E. Romanov; B. M. Rahimov; R. R. Yakovlev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The improved method of intraperitoneal plasty of umbilical hernia is considered in the article, the results and efficacy of its performance in the conditions of "one day" hospital department of surgery are estimated. The classical method of non-tension hernioplasty [1] is supplemented with surgical techniques - "peritoneal desquamation" and "peritoneodesis" [2] of the hernia sac. A special patented technical device was used in the course of surgical treatment. The suggested method of umbilical hernia plasty creates the conditions for traumatic interventions reduction, excludes the possibility of wound complications, reduces the operative intervention time and shows unique possibilities of using during the operations of natural, physiologically conditioned protective-adaptive systems of the body to activate restorative processes [4, 5].